Analysis of tripartite evolutionary game in the digital transformation of China's rural industries - Xu Weiwei (Frontiers in Sustainable Food Systems)
IntroductionPromoting the digital transformation of rural industry is a necessary path for the modernization and development of agriculture and rural areas.MethodsBased on the evolutionary game theory, this study constructs a tripartite evolutionary game model of the government, digital technology suppliers, and rural industry subjects. It analyzes the evolutionary stability strategies and influencing factors of each subject and carries out numerical simulation analysis using MATLAB.ResultsThe study found that: (1) The strategy choices of each game subject affect each other. The probability of the government's “encourage” strategy decreases with the increase of the probability of the digital technology supplier's active “supply” or the probability of the rural industry subject's active “adopt.” Similarly, a higher “encourage” probability by the government and a higher “adopt” probability by the rural industrial entities showed a higher “supply” probability by the digital technology providers. (2) The size of the initial probability and the change of each parameter have an important impact on the choice of behavioral strategy in the main body of the game. The evolutionary stability strategy eventually converges to the government choosing “encourage,” digital technology suppliers choosing “supply,” and rural industry subjects choosing “adopt.”DiscussionThis study biggest difference from previous research is that found that the evolutionary stability strategy ultimately converges to encourage the government, supply digital technology suppliers, and adopt rural industry entities. However, there are also shortcomings in the article, such as neglecting other stakeholders. this study finally proposes relevant suggestions from the government, digital technology suppliers, and rural industrial subjects.